Suplementasi Bacillus subtilis terhadap Produktivitas Ayam Petelur Skala Komersial: Supplementation of Bacillus subtilis to Productivity of Laying Hens on a Commercial Scale - Widodo, Andi Yekti; Sumiati; Tarigan, Ronald (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study, the impact of Bacillus subtilis probiotics on the productivity and faecal microbial variable of commercial laying hens in Indonesia was investigated. A total of 100,296 laying hens aged 18 weeks in a close house system were randomly allocated into two treatments with four replications per treatments. The applied treatments were T0 (control) and T1 (feed with probiotics). The experiment involved feeding laying hens with/without Bacillus subtilis strains 747 and 1781 (bacterial load of 1.5x108 cfu/kg feed, strain ratio of 1:1), collecting data on egg production, egg weight, feed consumption, and depletion from 20 to 26 weeks. Those variable were also observed from 18 to 19 weeks as pre-treatment data. Faecal samples were collected at 26 weeks for analysis of Escherichia coli, Clostridium perfringens, and lactic acid bacteria levels. The results revealed that administering Bacillus subtilis strains 1781 and 747 significantly increased daily egg production by 7.9% and reduced daily depletion by 65% at the end of the treatment phase. However, probiotic supplementation did not affect daily feed intake, feed conversion ratio, egg weight, or the levels of E. coli, C. perfringens, and lactic acid bacteria in the hens' faeces. These findings demonstrate the potential and feasibility of Bacillus subtilis strains 1781 and 747 in improving the productivity and health of laying hens of commercial-scale production. This information is valuable for the poultry industry in optimizing production practices. Key words: AGP, Bacillus subtilis, laying hen, probiotic, productivity